The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/nin.12285
|View full text |Cite
|
Sign up to set email alerts
|

Beyond and around mandatory reporting in nursing practice: Interrupting a series of deferrals

Abstract: Nurses are well positioned to contribute to child protection efforts but are underutilised. This paper describes a critical discursive analysis of nursing responses to child neglect and abuse (CN&A) in British Columbia, Canada. Legal and practice guidelines were analysed alongside nurse interview texts, offering a glimpse into how nurses prevent CN&A in their everyday practice with families. Results show how the primacy of mandatory reporting to child protection authorities coordinates a series of deferrals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This results in a clinical practice that can place nurses in the position of perceiving that they are simultaneously supporting and policing families. Over the past 20 years, accumulating evidence suggests that there is increasing concern that these hard-won trusting relationships may be at risk for irrevocable damage, in particular from involvement in child protection issues (Browne et al, 2010; Crisp & Green Lister, 2004; Davidov et al, 2012; Einboden et al, 2019; Lines et al, 2017; Mulcahy & McCarthy, 2008; Peckover, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This results in a clinical practice that can place nurses in the position of perceiving that they are simultaneously supporting and policing families. Over the past 20 years, accumulating evidence suggests that there is increasing concern that these hard-won trusting relationships may be at risk for irrevocable damage, in particular from involvement in child protection issues (Browne et al, 2010; Crisp & Green Lister, 2004; Davidov et al, 2012; Einboden et al, 2019; Lines et al, 2017; Mulcahy & McCarthy, 2008; Peckover, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…CDA's orientation to addressing social injustice offers an opportunity to depart from the usual research focus on the types of violence children endure, instead encouraging an investigation of relations and operations of power within child protection practices (Einboden, 2017). It was chosen as a methodology to examine nursing responses to CN&A, because of the orientation to produce knowledge as a resource for social action: to disrupt discriminatory child protection practices; and to shape equitable responses to children's safety that are respectful of and meaningful to children and their families (see Einboden, 2017; Einboden et al, 2019).…”
Section: An Example: Using Cda With Figuration To Analyse Nursing Res...mentioning
confidence: 99%
“…Nurses, the largest group of health professionals, are among the occupational groups in contact with children at increased risk of abuse and neglect (Lines et al, 2018). However, many studies have reported that nurses face barriers to reporting child maltreatment cases (Einboden et al, 2019; Elarousy & Abed, 2019; Lee & Kim, 2018). As a result of a study conducted with 930 nurses in Australia, it was reported that nurses' knowledge and attitudes differed toward different types of maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have reported that nurses face barriers to reporting child maltreatment cases (Einboden et al, 2019;Elarousy & Abed, 2019;Lee & Kim, 2018). As a result of a study conducted with 930 nurses in Australia, it was reported that nurses' knowledge and attitudes differed toward different types of maltreatment.…”
mentioning
confidence: 99%